Mother's Image in Joko Pinurbo's Poetry Collection Surat Kopi - Erwis; Else Liliani; Anwar Efendi; Hartono (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to discuss the image of mothers in the poetry collection Surat Kopi by Joko Pinurbo. The research method used is descriptive qualitative using a hermeneutic approach. The data of this research is in the form of poetry quotations that contain words or phrases containing images of mothers, both physical, psychological, and social images. The data is obtained from the poems contained in the poetry collection Surat Kopi by Joko Pinurbo. The poems used as objects are 18 poems, with consideration of the suitability of the issues raised in the study. The results of this study describe the image of a mother as a woman who has physical, psychological, and social aspects. The mother depicted is a mother who is strong and strong in raising her children and a figure who loves and cares about her children. The poet more dominantly displays the psychological and social aspects of a mother in her poems.